Indoor Radon Concentration Measurements At Hebron University Campus :A Case Study - Fakhri I. Hasan (مجلة جامعة النجاح للأبحاث العلوم الطبيعية)
TASTRAK, a solid state nuclear track detector has been used to measure indoor radon concentrations at Hebron University. Fifty- four radon pot detectors were mounted in the four university buildings. It was found that the radon concentrations vary considerably from about 1 Bq/m 3 to 250 Bq/m3 The average radon concentrations vary from 20.5 Bq/m3 in the Main Building to 41.3 Bq/m3 in the Agriculture Building. The average radon concentration in the four buildings is found to be 29.8 Bq/m 3. This leads to an average effective dose equivalent of 1.49 mSvly. This dose is slightly higher than the global value of 1.3 mSv/y. Elevated radon concentrations have been found in few rooms. However, these concentrations are well below the action level of 150 Bq/m3.